Embryo yield in llamas synchronized with two different intravaginal progesterone-releasing devices and superovulated with eCG - Aller Atucha, Juan Florencio (2015)
The objectives of this study were to compare the effects of two intravaginal devices (ID) containing the same dose (0.5 g) of progesterone (P4) on subsequent ovarian response, embryo production and circulating P4 concentration profile in llamas (Lama glama) treated with equine chorionic gonadotropin (eCG) for ovarian superstimulation. Female llamas were randomly assigned (n = 10 llamas per group) to one of the following groups and treated (Day 0) with an ID containing 0.5 g of vegetal P4 to synchronize the emergence of a new follicular wave: i) DIB 0.5® and ii) Cronipres M15®. On Day 3 llamas were intramuscularly treated with 1000 IU of eCG. The IDs were removed on Day 7. Llamas were naturally mated (Day 9) and treated with GnRH analogue to induce ovulation. A second mating was allowed 24 h later. Embryos were collected between 7 and 8 days after the first mating. Blood samples were taken every day from Day 0 to Day 7 to measure circulating P4 concentrations. The results indicated that DIB device maintained greater plasma P4 levels as compared to Cronipres until Day 2. However, the mean (± SD) number of corpora lutea and recovered embryos was not affected (p < 0.05) by the type of ID (5.3 ± 2.6 vs 4.2 ± 2.2 and 3.5 ± 2.7 vs 2.6 ± 3.0 for DIB and Cronipres, respectively). In conclusion, both DIB and Cronipres devices can be successfully used to synchronize the emergence of follicular wave prior to a single dose of eCG in superovulation protocol in llamas.